The Elgar companion to marketing and the sustainable development goals - Voola, Ranjit; Carlson, Jamie; Makkar, Marian; Bosangit, Carmela; Goswami, Paromita (Elgar companions to the sustainable development goals., 2025)
"This interdisciplinary Companion explores the pivotal role of marketing in advancing the Sustainable Development Goals (SDGs). It provides diverse perspectives on how marketing strategies can drive sustainable development including sustainable consumer behaviour and emphasises the importance of ethical considerations, stakeholder engagement and innovative approaches to positively impact society. Leading scholars and practitioners from across 15 countries discuss key themes such as consumer behaviour, strategic marketing, Base of the Pyramid marketing, technological innovations and marketing education. Real-world examples and global perspectives are used to demonstrate that marketing is not solely about selling and can also be a powerful tool for creating positive change for people and the planet. The Companion investigates how cutting-edge technologies including AI, blockchain and the Internet of Things can enable responsible consumption and transparency. It further highlights the necessity for marketers to actively shape the post-2030 framework to align with evolving global sustainability goals. Scholars and students of marketing, international business, sustainability, organisation studies and development studies will greatly benefit from this comprehensive Companion. Timely and engaging, it is also an essential resource for policymakers and practitioners in marketing and the business sector, as well as those working with the SDGs"--